ISU-ISU EKONOMI DAN PENGURUSAN DI MALAYSIA - Abdul Aziz Jemain; Lukman Z. Mohamad; Azmi Abdul Manaf; Rokiah @ Rozita Ahmad (Prentice Hall, 2001)
Issues on the development and population in Malaysia; papers of a seminar.